2014
DOI: 10.1371/journal.pone.0094668
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Radioiodinated Triazolopyrimidine Probe for Nuclear Medical Imaging of Fatty Acid Binding Protein 4

Abstract: Fatty acid binding protein 4 (FABP4) is the most well-characterized FABP isoform. FABP4 regulates inflammatory pathways in adipocytes and macrophages and is involved in both inflammatory diseases and tumor formation. FABP4 expression was recently reported for glioblastoma, where it may participate in disease malignancy. While FABP4 is a potential molecular imaging target, with the exception of a tritium labeled probe there are no reports of other nuclear imaging probes that target this protein. Here we designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…4). Cell differentiation and FABP4 expression in differentiated adipocytes were confirmed by Oil red O staining and western blot analysis, respectively, in a similar way to that described in our previous report [9]. [ 18 F]FTAP1 showed significantly higher radioactivity in adipocytes than 3T3-L1 preadipocytes.…”
Section: In Vitro Evaluation Of [ 18 F]ftap1supporting
confidence: 85%
See 3 more Smart Citations
“…4). Cell differentiation and FABP4 expression in differentiated adipocytes were confirmed by Oil red O staining and western blot analysis, respectively, in a similar way to that described in our previous report [9]. [ 18 F]FTAP1 showed significantly higher radioactivity in adipocytes than 3T3-L1 preadipocytes.…”
Section: In Vitro Evaluation Of [ 18 F]ftap1supporting
confidence: 85%
“…In the present study we developed [ 18 F]FTAP1 for in vivo PET imaging of FABP4, which is closely related to CAA functions [5], tumor progression [5], and atherosclerotic plaque instability [13]. This probe is based on our previous radioiodinated probe, [ 123/125 I]TAP1 [9]. [ 18 F]FTAP1 showed high affinity and selectivity for FABP4, adequate cellular membrane permeability, and high uptake into differentiated adipocytes expressing FABP4 that could be perfectly blocked by a selective FABP4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematopoietic stem cell transplantation has been one of the available therapies to treat AML [6]. Previous studies have demonstrated that evaluating the efficiency of both ESCs and iPSCs in cardiac cell therapy in an in vitro analysis is currently the focus of mainstream research [7, 8], but in recent years, iPSCs have become a great alternative for the treatment of AML [9]. These cells share many similarities with embryonic stem cells (ESCs), which serve as a model to study molecular embryogenesis and have a great potential for applications in regenerative medicine [10], including multilineage differentiation and self-renewal [11].…”
Section: Introductionmentioning
confidence: 99%